Integrating TSTS Model into Digital Flipbooks: A Strategy to Foster Numerical and Scientific Problem-Solving Ability - Annisa Fauzana; Suherman; Yerizon; Edwin Musdi (Postgraduate, University of Mataram, 2026)
This study aimed to develop and evaluate a Two Stay Two Stray (TSTS)-integrated digital flipbook electronic worksheet (E-LKPD) designed to enhance mathematical problem-solving abilities among eighth-grade students. Employing the Plomp research and development model, the product underwent systematic expert validation, iterative usability testing, and classroom-based field evaluation. Results indicated that both the teaching module and E-LKPD achieved